1998
DOI: 10.1016/s0895-7061(98)00025-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cardiovascular Effect of 1,25-Dihydroxycholecalciferol in Essential Hypertension

Abstract: A role for vitamin D in the pathophysiology of essential hypertension has frequently been suggested, but acute direct effects on blood pressure, cardiac output, renal hemodynamics, or hormones have not previously been demonstrated. The rapid effects of 1,25-dihydroxycholecalciferol (1,25-D) were assessed over 120 min after a bolus injection (0.02 microg/kg body weight) in eight men with essential hypertension and in nine healthy men. A placebo group of 10 healthy men was also included. Ionized calcium was moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
16
1
2
Order By: Relevance
“…The single study that has investigated the short-term effect of vitamin D on cardiovascular hemodynamics showed that vitamin D caused rapid changes in patients with essential hypertension but not in controls. 76 In patients with essential hypertension, the cardiac output decreased by Ϸ15% within 2 hours of intravenous administration of 1␣,25(OH) 2 D 3 (0.2 /kg). This was associated with transient smaller increases in pulse rate and mean blood pressure, suggesting that 1␣,25(OH) 2 D 3 had a nongenomic effect to increase peripheral resistance.…”
Section: Nongenomic Effects Of Vitamin D On Peripheral Vascular Resismentioning
confidence: 99%
“…The single study that has investigated the short-term effect of vitamin D on cardiovascular hemodynamics showed that vitamin D caused rapid changes in patients with essential hypertension but not in controls. 76 In patients with essential hypertension, the cardiac output decreased by Ϸ15% within 2 hours of intravenous administration of 1␣,25(OH) 2 D 3 (0.2 /kg). This was associated with transient smaller increases in pulse rate and mean blood pressure, suggesting that 1␣,25(OH) 2 D 3 had a nongenomic effect to increase peripheral resistance.…”
Section: Nongenomic Effects Of Vitamin D On Peripheral Vascular Resismentioning
confidence: 99%
“…These observations also hold true in humans. Jespersen et al [23] observed that pharmacological doses of vitamin D 3 increased the blood pressure simultaneous with a decrease in cardiac output in patients with essential hypertension, suggesting that the blood pressure increase is mainly due to an effect on peripheral vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the evidence is found in small, short clinical trials or case studies. In a study of individuals with hypertension, 1α,25 (OH) 2 D administration resulted in a transient increase in blood pressure 120 min after a bolus injection (0.02 μg/kg body weight) [40], whereas no change in blood pressure was observed in the nonhypertensive controls. In contrast, in a Japanese case report, blood pressure decreased from 145/96 mm Hg to 128/85 mm Hg after 1α,25(OH) 2 D administration, as did plasma renin activity [32].…”
Section: The Effects Of 1α25(oh) 2 D On Blood Pressurementioning
confidence: 98%